Guidelines for ultrasound owners and owners of clinics, diagnostic centres, nursing homes and hospitals - Mani, Sanjeev (Indian Journal of Radiology and Imaging, 2012)
These are guidelines that are required for ultrasound owners for registration and use of ultrasound machines and are applicable across India. A brief description of the violations and penalties has also been listed.
Keywords: PNDT Guidelines; nursing home; diagnostic centre; rules; violations